Le probabilisme comme stratégie de compréhension interculturelle dans le Pérou colonial - Jaime Villanueva Barreto (Droit et Cultures, 2011)
The purpose of this article is to determine the role of probabilism in the construction of the moral order in Peru.  Toward that end, we offer the following theses:  (1) in Peru, Jesuit probabilism was the most efficient strategy for bringing about a “negotiated morality” between the universalist claims of European culture and the particularisms of local lifeways; (2) in the course of that effort, a moral system was constituted allowing for intercultural understanding by transferring moral judgments from the domain of theory (causal and nomological explication) to that of opinion (explication of reasons and circumstances) – that is, for lack of certainty, decisions were necessarily based on opinions of probability; (3) the attempt to arrive at an understanding between Hispanic and Andean categories in effect created a new culture that characterizes life in Peru, where – interestingly – hierarchical authority blends with bureaucratic laxity, rebellion with servitude, exclusion with attachment to order, the most unimaginable chaos with obstruction to all change that would allow for the foundation of a homogeneous modernity.  Our argument will be limited to the philosophical aspect of the debate over probabilism in Peru, as a position that stimulated the reflections of the Peruvian elite.